1946
DOI: 10.1136/bmj.2.4482.817
|View full text |Cite
|
Sign up to set email alerts
|

"Purpura Provocata" in Pellagra

Abstract: MEDICAL MEMORANDA MEDBRATSOURNAL 817 from May 18 onwards, starting with 2 ml. I.M. on alternate days, the dose later being increased to 4 ml. Iron was given for the anaemia. The temperature swing gradually diminished in height, and became normal and remained so after the nineteenth injection (June 22). Clinically there was marked improvement, with cessation of sweats and diminution in the size of the spleen, and the white blood cells showed a steady increase. Blood counts were as follows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1949
1949
1976
1976

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Nonetheless, the highest tryptamine levels were again obtained in the uppermost leaves of plants receiving ammonium sulfate, particularly when fertilizers were applied at high rates (Parmar 197 s). DISCUSSION From the studies of Dickinson, Carlson and associates (1961,1968,1972) Marten and associates (Marten 1973) have shown that proportions of the several tryptamines in RCG are under strong genetical control, but that their concentration may be modified by nutritional conditions; moreover, a relationship to differential palatability of RCG strains has been related to differential alkaloid concentration (Simons 1970;Simons and Marten l97l). Ranchers have also noted rnarked changes in palatability of RCG after applications of fertilizer.…”
mentioning
confidence: 99%
“…Nonetheless, the highest tryptamine levels were again obtained in the uppermost leaves of plants receiving ammonium sulfate, particularly when fertilizers were applied at high rates (Parmar 197 s). DISCUSSION From the studies of Dickinson, Carlson and associates (1961,1968,1972) Marten and associates (Marten 1973) have shown that proportions of the several tryptamines in RCG are under strong genetical control, but that their concentration may be modified by nutritional conditions; moreover, a relationship to differential palatability of RCG strains has been related to differential alkaloid concentration (Simons 1970;Simons and Marten l97l). Ranchers have also noted rnarked changes in palatability of RCG after applications of fertilizer.…”
mentioning
confidence: 99%